2021
DOI: 10.4236/jwarp.2021.131003
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Analyses of Controlled Release of Potassium Permanganate Encapsulated in Polycaprolactone

Abstract: Potassium permanganate (KMnO 4) has been used widely as an oxidant for remediation of contaminated soil and water systems. The present study evaluates the release of this oxidant from Polycaprolactone (PCL) polymer as part of a patented controlled release process (CRP) to be applied for targeted removal of contaminants from water. KMnO 4 was encapsulated into PCL at a 1:5 oxidant to polymer ratio and placed in batch reactor systems with reagent water to be evaluated over a 96 hour period. SEM images showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 34 publications
4
6
0
Order By: Relevance
“…The present study focused on a CRBP system to measure the discharge of varied levels of KMnO 4 oxidant into aqueous systems. In the batch systems, dissolution of the PCL polymer releasing the KMnO 4 corresponded to what had been seen in other controlled-release systems [5] [23] [25] and, more specifically, with systems utilizing the same polymer oxidant system [20] [27]. As the amount of KMnO 4 in the PCL polymer pellets increased, a greater fraction of the oxidant was released as a function of time (Figure 2).…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…The present study focused on a CRBP system to measure the discharge of varied levels of KMnO 4 oxidant into aqueous systems. In the batch systems, dissolution of the PCL polymer releasing the KMnO 4 corresponded to what had been seen in other controlled-release systems [5] [23] [25] and, more specifically, with systems utilizing the same polymer oxidant system [20] [27]. As the amount of KMnO 4 in the PCL polymer pellets increased, a greater fraction of the oxidant was released as a function of time (Figure 2).…”
Section: Resultssupporting
confidence: 66%
“…These SEM images show the circular cavities or crevices within the polymer surface increase as a function of time of pellet contact in water increases. This resulting growth in cavities due to dissolution has also been seen in similar controlled release systems using KMnO 4 [15] [24] [27]. The growing crevices displayed in the SEM images (Figure 5) as time increased were indicative of the biphasic trends shown by the release data (Figure 4).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Table 1 provides the list of chemicals studied in the paper ( Huling and Pivetz, 2002 ; Khodaveisi et al., 2011 ; Miao et al., 2015a , 2015b , and 2015c ). Permanganate is available as a salt (KMnO4 and NaMnO4) and has been widely used as an ISCO oxidant for the remediation of contaminated soil and groundwater systems ( King et al., 2021 ; Khodaveisi et al., 2011 ; Li and Schwartz, 2004 ). Previous studies ( Liu et al., 2014 ; Waldemer and Tratnyek, 2006 ) have suggested that permanganate is less powerful than other oxidative species but reacts quickly with specific contaminants including chlorinated ethenes.…”
Section: Introductionmentioning
confidence: 99%